PENERAPAN METODE REPEAT AFTER ME DALAM MELATIH PENGUCAPAN KOSAKATA BAHASA INGGRIS DI SMA MUHAMMADYAH 2 PALANGKA RAYA - Fitria Indriani Fitri; Nurul Wahdah; Nanik Yulianingsih (LP3K Lampung, 2023)
Errors in pronouncing English vocabulary are a very common problem experienced by students. What causes the low ability of students' English vocabulary pronunciation is the influence of previous educational stages which do not force students to practice pronouncing English vocabulary, are not used to it, and lack confidence. The purpose of holding this service is to motivate students to develop their English vocabulary pronunciation skills so that they are not far behind in the current millennial era. The method applied during this activity process uses repeat after me (repeat after me). The students focused on the sense of hearing while paying attention to the gestures and movements that were practiced simultaneously when reciting vocabulary to clarify the meaning of the English word. The results obtained by this service show that the application of the repeat after me method can help students be more active in practicing English pronunciation vocabulary and first the English teachers who teach there can be motivated to invite students to practice together using the repeat after me method more often.